2022
DOI: 10.5194/bg-19-313-2022
|View full text |Cite
|
Sign up to set email alerts
|

Net soil carbon balance in afforested peatlands and separating autotrophic and heterotrophic soil CO<sub>2</sub> effluxes

Abstract: Abstract. Peatlands are a significant global carbon (C) store, which can be compromised by drainage and afforestation. Quantifying the rate of C loss from peat soils under forestry is challenging, as soil CO2 efflux includes both CO2 produced from heterotrophic peat decomposition and CO2 produced by tree roots and associated fungal networks (autotrophic respiration). We experimentally terminated autotrophic below-ground respiration in replicated forest plots by cutting through all living tree roots (trenching)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…1d, e), reflecting the similar dynamics of these two effluxes in response to WT decline. Recent annual measurements also revealed strong linear correlation between SR and HR from temperate to boreal pristine and drained peatlands 40 . These results collectively indicated that increases in SR from global pristine peatlands under WT decline were mainly due to HR rather than AR.…”
Section: Resultsmentioning
confidence: 96%
“…1d, e), reflecting the similar dynamics of these two effluxes in response to WT decline. Recent annual measurements also revealed strong linear correlation between SR and HR from temperate to boreal pristine and drained peatlands 40 . These results collectively indicated that increases in SR from global pristine peatlands under WT decline were mainly due to HR rather than AR.…”
Section: Resultsmentioning
confidence: 96%
“…However, peatlands can be now optionally accounted under EU rules until 2026, afterwards accounting of this category becomes mandatory (EU 2018/841). Furthermore, recent study in Scotland (Hermans et al, 2022) shows that afforestation of previously drained peatlands and further forest management activities can even increase soil carbon stocks due to litter input which exceed heterotrophic peat decomposition, while default reporting guidelines (Tier 1 level, IPCC 2006) still request reporting of GHG emissions due to drainage of organic soils. Hence, increasing reporting accuracy by setting reliable emission factors on the national levels and moving to higher Tier level, as well as aligning reporting and accounting rules under different mechanisms would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Using the trenching method, Tomotsune et al [31] found that the soil temperature response of Rh is higher than that of Ra in a broad-leaved secondary forest. The trenching method allows Ra and Rh to be physically separated [3,32,33], and some studies have…”
Section: Discussionmentioning
confidence: 99%
“…Using the trenching method, Tomotsune et al [31] found that the soil temperature response of R h is higher than that of R a in a broad-leaved secondary forest. The trenching method allows R a and R h to be physically separated [3,32,33], and some studies have separated not only R h but also soil organic matter respiration [12] and mycorrhizal respira-tion [12,34]. The contribution of R a is 45.8% among forest sites around the world [10,11].…”
Section: Discussionmentioning
confidence: 99%